2023
DOI: 10.3390/chemosensors11030165
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy for Differentiating Oak Barrel Aged and Non-Oak Barrel Aged Wines by Using UHPLC–HRMS Combined with Chemometrics

Abstract: The time involved and the high economic cost of using oak barrels to age wines have led to a significant price difference compared to non-oak barrel aged wines and may lead to some fraudulent sales in the market. In this study, an untargeted metabolomic strategy was developed to detect the metabolite composition of oak barrel aged and non-oak barrel aged wines in both positive and negative ion modes by using UHPLC–HRMS combined with the recently developed chemometric method AntDAS. The results of partial least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…Our results revealed the effectiveness of 1 H-NMR metabolomics for the differentiation of wine metabolome related to different types of aging container material. This observation was in agreement with the works of Lv et al [ 33 ] and Maioli et al [ 21 ] who also found significantly higher abundances of various metabolites in wooden-barrel-aged wines compared to the ones matured in other kinds of containers. As already discussed for the total phenolic content, a large variety of compounds including both aroma volatile and non-volatile metabolites can be extracted from oak woods and transferred into the wine during barrel aging [ 18 ].…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Our results revealed the effectiveness of 1 H-NMR metabolomics for the differentiation of wine metabolome related to different types of aging container material. This observation was in agreement with the works of Lv et al [ 33 ] and Maioli et al [ 21 ] who also found significantly higher abundances of various metabolites in wooden-barrel-aged wines compared to the ones matured in other kinds of containers. As already discussed for the total phenolic content, a large variety of compounds including both aroma volatile and non-volatile metabolites can be extracted from oak woods and transferred into the wine during barrel aging [ 18 ].…”
Section: Resultssupporting
confidence: 93%
“…Our results revealed the effectiveness of 1 H-NMR metabolomics for the differentiation of wine metabolome related to different types of aging container material. This observation was in agreement with the works of Lv et al [33] and Maioli et al [21] who also found S2.…”
Section: Influence Of Aging Container Type On the Metabolite Profiles...supporting
confidence: 94%
See 2 more Smart Citations